2019
DOI: 10.1186/s13071-019-3524-6
|View full text |Cite
|
Sign up to set email alerts
|

Metazoan parasite infracommunities of the dusky flounder (Syacium papillosum) as bioindicators of environmental conditions in the continental shelf of the Yucatan Peninsula, Mexico

Abstract: Background We assessed metrics of the metazoan parasite infracommunities of the dusky flounder ( Syacium papillosum ) as indicators of aquatic environmental health of the Yucatan Shelf (YS) prior to oil extraction. We sampled the dusky flounder and its parasites along the YS, mostly during the 2015 north wind season (November–April). Our aims were: (i) to determine whether the parasite infracommunity metrics of S. papillosum exhibit significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…These differences in ectoparasite composition might be due to the physicochemical (water quality, nutrients, and water flow rates) and biological characteristics of the regions along the south-southwest coast from Tabasco to Campeche, and along the south-southeast coast in the Yucatán Peninsula. This hypothesis has been partially tested through a comparative study of the parasitofauna of flounder fish from the Yucatán Peninsula (i.e., Syacium papillosum and Syacium gunteri ) ( Vidal-Martínez et al 2019 ). Vidal-Martínez et al (2019) found variation in the parasite composition associated with environmental variables, suggesting the existence of two subregions in the Yucatán Peninsula (the Campeche Sound and the Yucatán Shelf).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences in ectoparasite composition might be due to the physicochemical (water quality, nutrients, and water flow rates) and biological characteristics of the regions along the south-southwest coast from Tabasco to Campeche, and along the south-southeast coast in the Yucatán Peninsula. This hypothesis has been partially tested through a comparative study of the parasitofauna of flounder fish from the Yucatán Peninsula (i.e., Syacium papillosum and Syacium gunteri ) ( Vidal-Martínez et al 2019 ). Vidal-Martínez et al (2019) found variation in the parasite composition associated with environmental variables, suggesting the existence of two subregions in the Yucatán Peninsula (the Campeche Sound and the Yucatán Shelf).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis has been partially tested through a comparative study of the parasitofauna of flounder fish from the Yucatán Peninsula (i.e., Syacium papillosum and Syacium gunteri ) ( Vidal-Martínez et al 2019 ). Vidal-Martínez et al (2019) found variation in the parasite composition associated with environmental variables, suggesting the existence of two subregions in the Yucatán Peninsula (the Campeche Sound and the Yucatán Shelf). However, a comparative study of the parasitofauna of Sphoeroides spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their complex life cycles involving multiple intermediate hosts and their sensibility to specific environmental conditions allow many endoparasites to be used as environmental indicators (Palm 2011;Kleinertz et al 2016;Neubert et al 2016;Vidal-Martínez et al 2019). Marine parasitology is still a globally underrepresented field in aquatic biodiversity and ecological research, although it is an essential tool in aquatic health studies and to get insights into fish diet, fish stocks, migration, and trophic positions (Marcogliese and Scholz 1999;Marcogliese 2003;Kleinertz et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These PAHs with terrestrial origin are transported by rivers or air to the sea (Baek et al 1991;Morrison and Boyd 1998). In the southern Gulf of Mexico, coastal and offshore petroleum extraction is a significant economic activity (García-Cuellar et al 2004;Vidal-Martínez et al 2019) that, together with natural hydrocarbon release from oil seeps, exposes marine organisms to hydrocarbons. Additionally, processed hydrocarbons, such as motor oils, diesel, and lubricants, together with other contaminants, such as heavy metals, pesticides, and fertilizers (e.g., N and P in different compounds), are also transported from the continent and released in marine waters (Morrison and Boyd 1998).…”
Section: Introductionmentioning
confidence: 99%